Q: What is the nth term of the sequence 18 12 6 0 -6?

Write your answer...

Submit

Related questions

The sequence has a difference of 10, so the nth term starts with 10n. Then to get to -8 from 10 you need to subtract 18. So the nth term is 10n - 18.

Well, it would depend what the sequence was...? If the sequence was 2,4,6,8,10,12,14,16,18,20, then the 9th term would be 18!

18 - 6n

The nth term of the sequence is (n + 1)2 + 2.

If you mean: 6 12 18 24 then the nth term is 6n

The nth term in this sequence is 4n - 2.

The nth term in this arithmetic sequence is an=26+(n-1)(-8).

The 'n'th term is [ 13 + 5n ].

The 'n'th term is [ 13 + 5n ].

The 'n'th term is [ 13 + 5n ].

The 'n'th term is [ 13 + 5n ].

The 'n'th term is [ 13 + 5n ].

58

The nth term of that series is (24 - 6n).

The nth term is 18 -3n and so the next term will be 3

the sequence is Un=2n2

i relly dont know tony

For {12, 15, 18} each term is the previous term plus 3; a general formula for the nth term is given by t(n) = 3n + 9. For {12, 24, 36} each term is the previous term plus 12; a general formula for the nth term is given by t(n) = 12n.

t(n) = (-5n4 + 62n3 - 247n2 + 334n - 36)/6

The next term is 45 because the numbers are increasing by increments of 3 5 7 9 and then 11

All you have to do is add 5 each time(x+5) It's 43

The nth term is 7n-3 and so the next term will be 39

12, 8

Un = 5n - 2

The nth term of an AP with initial term a (= u{1}) and common difference d is given by: u{n} = a + (n - 1)d In this case: a = 6 d = (12 - 6) = 6 → u{n} = 6 + (n - 1)6 But this can be simplified: u{n} = 6 + (n - 1)6 = 6 + 6n - 6 = 6n